Clinical assessment of bronchodilator drugs delivered by aerosol. Issue 2 (March 1973) - Shenfield, Gillian M.; Paterson, J. W.
Abstract : A method is described for the early clinical evaluation of bronchodilator aerosols. It is simple to perform, and an accurate estimate of potency can be obtained in a small number of patients. Using this method, three new sympathomimetic drugs, Th 1165a, salmefamol, and rimiterol, have been tested. All proved to be active bronchodilators and were equipotent with isoprenaline or salbutamol.